Spatial and temporal variations in the environmental and biological characteristics of the Turyanchay River basin, Azerbaijan - Aliyev, Saleh; Farzali, Shabnam; Durrani, Omerhan (Taylor & Francis Inc, 2023)
This is the first comprehensive examination of the Turyanchay River in Azerbaijan, focusing on water quality (WQ), contamination, and biodiversity at four different locations: Gabala, Agdash, Udjar and Zardab. The study analysed nutrient (nitrate, ammonium, phosphate) and metal/metalloid (Pb, Cu, Ni, Zn, Mn, Cr, Cd, Fe and Al) contamination levels, as well as the diversity of macrozoobenthos in the river, birds and vegetation. The chemical and biological oxygen demands (COD and BOD), including WQ index (WQI) were also determined for the river. The results showed no significant difference in the levels of nutrients, metal/metalloid, COD, BOD, WQI and macrozoobenthos diversity across different locations (p > .05). However, they revealed temporal fluctuations, with their highest levels being recorded during the warmer months (July and August) and the lowest during the colder months (March and November). The estimated WQI, ranging from 19.6 to 43.6, indicated that the water in the Turyanchay River is safe for household and consumption purposes. Up to 83 species of macrozoobenthos were identified, with Hydropsychidae and Chironomidae showing the highest species richness, followed by Coenagrionidae, Psychomyiidae, Ceratopogonidae, Baetidae, Naididae and Gammaridae. Eighteen bird species, consisting of 11 terrestrial and 7 aquatic birds, were recorded, with eight of these species belonging to the Order Charadriiformes. A total of 42 different plant species belonging to 17 families were identified in the Turyanchay River basin, with Fabaceae being the most widely distributed, followed by Asteraceae and Typhaceae. This study provides important baseline data for the Turyanchay River, offering insights into its freshwater environment and biodiversity, and should support future monitoring efforts.
Keywords: Macrozoobenthos; metal; metalloid; nutrient pollution; ornithofauna; vegetation